Enhancing the urban identity of coastal public spaces in the city of Lattakia- South Corniche case study - دلالة ليليان; جورج قنصلية; طارق بركات (Latakia University Journal -Engineering Sciences Series, 2024)
Coastal public space is considered one of the important and distinctive characteristics of cities and urban coastal communities. Recently, as a result of rapid growth, most coastal public spaces have become similar and lost their identity. Lattakia city has many coastal public spaces. However, it suffers from the absence of meaning in the identity of the coastal public space, and the weak role of its current planning in enhancing that identity. Therefore, the question that arises is to what extent is the current planning of coastal public spaces in the city of Lattakia able to enhance its identity? This paper aims to provide reference guidelines for the future planning and design of coastal public spaces in the city of Latakia, in a way that enhances its identity. Research Methodology: The research method used is a descriptive analytical method, relying on studies, observation and interviews as sources of data, and identifying forms of identity of the space, including all relevant elements. Results: The results of this research showed that the studied state suffers from a set of problems that limit its ability to enhance its urban identity. The research concluded with recommendations that could contribute to the development of coastal public space planning.